Training in Writing, Citation and Publication of Scientific Articles - Kuswanto, Kuswanto; Abidin, Zaenal; Rochbani , Ita Tryas Nur; Aprianto , Iwan (CV. Zabags Qu Publish, 2024)
The aim of this service activity is to provide training and improve skills in writing scientific articles. The methods used are discussion, lecture, question and answer, and mentoring. The location of the service activities was held at the Al-Mujaddid Sabak Islamic Institute with students participating. The results of the scientific article publication training activities for students have an impact on increasing knowledge about how to write quotations, abilities and skills in writing narratives, etc. Based on the results of the questionnaire from this service activity, participants gained knowledge, skills in writing and publication of scientific articles in a fairly good category.